Roofline Analysis and Performance Optimization of the MGB Hydrological Model - Freitas, Henrique; Mendes, Celso Luiz (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2019: Anais do XX Simpósio em Sistemas Computacionais de Alto Desempenho, 2019)
The Roofline model gives insights about the performance behavior of applications bounded by either memory or processor limits, providing useful guidelines for performance improvements. This work uses the Roofline model on the analysis of the MGB model that simulates hydrological processes in largescale watersheds. Real-world input data are used to characterize the performance on two multicore architectures, one with only CPUs and one with CPUs/GPU. The MGB model performance is improved with optimizations for better memory use, and also with shared-memory (OpenMP) and GPU (OpenACC) parallelism. CPU performance achieves 42.51 % and 50.17 % of each system’s peak, whereas GPU performance is low due to overheads caused by the MGB model structure.